Cryosphere response resolves conflicting evidence for the timing of peak Holocene warmth on Baffin Island, Arctic Canada. (15th July 2019) - Pendleton, Simon; Miller, Gifford; Lifton, Nathaniel; Young, Nicolás
Abstract: Holocene paleotemperature reconstructions across the western Arctic suggest strong spatial variations in air temperature despite zonally uniform Northern Hemisphere insolation forcing. Although most paleotemperature reconstructions across the Eastern Canadian Arctic place the Holocene thermal maximum >3 kyr after peak summer insolation, other records indicate maximum summer warmth was coincident with peak summer insolation. To address this discrepancy, we use radiocarbon inventories in plants and rocks recently exposed by receding ice caps to reconstruct early Holocene changes in glacier dimensions, a reliable proxy for summer air temperature. Fourteen radiocarbon ages from newly exposed plants in growth position collected at the margins of eight retreating ice caps on Baffin Island indicate ice caps expanded 9.3 ± 0.3 ka, and remained over these sites until recent summer warming, indicating peak early Holocene summer warmth occurred prior to ∼9.3 ka. We test this conclusion using in situ cosmogenic 14 C ( in situ 14 C) inventories in rocks at four sites with dated plants. In situ 14 C production simulations using realistic Holocene ice-cover histories constrained by plant 14 C ages show that measured in situ 14 C concentrations are consistent with centuries to millennia of pre-9.3 ka exposure, followed by continuous ice burial. The combination of plant and in situ 14 C data provide firm evidence that the Eastern Canadian Arctic experienced peak Holocene summer warmth prior to ∼9.3 ka, consistent with peak summer insolation, followed by continuously colder summers until modern warming. Highlights: 14 C inventories in plants and rocks exposed by receding ice reconstruct early Holocene glacier changes on Baffin Island. Ice caps buried sample sites at 9.3 ± 0.3 ka and remained over these sites summer warming. Simulations of radiocarbon production in rock surfaces are consistent with centuries to millennia of pre-9.3 ka exposure. This new evidence suggests that Baffin Island experienced peak Holocene summer warmth prior to ∼9.3 ka.